Nonlinear buckling of axially compressed FG‐GRCL stiffened cylindrical panels with a piezoelectric layer by using Reddy's higher‐order shear deformation theory. Issue 11 (23rd July 2022) - Nam, Vu Hoai; Dong, Dang Thuy; Van Doan, Cao; Phuong, Nguyen Thi
Abstract: This paper proposed a new analytical approach for the nonlinear buckling behavior of axially compressed functionally graded graphene reinforcement composite laminated (FG‐GRCL) stiffened cylindrical panels with the piezoelectric layers resting on the Pasternak's elastic foundation in the uniformly distributed temperature change. A design for the reinforcement of stiffened cylindrical panels is applied where the polymer matrixes of panels and stiffeners are reinforced by graphene sheets. The effects of FG‐GRCL stiffeners are modeled using the improved smeared stiffener technique, which is developed by applying the anisotropic higher‐order shear deformation beam theories for curved and straight stiffeners. The fundamental formulations are obtained by applying Reddy's higher‐order shear deformation theory (HSDT), and taking into account the von Kármán geometrical nonlinearities. The algebraically nonlinear equilibrium equations are achieved by employing Galerkin's procedure, and then they can be solved by using the ordinary calculation process. Some important remarks on the nonlinear buckling of stiffened FG‐GRCL cylindrical panels are archived from the numerical investigation process. Abstract : The nonlinear thermo‐electro‐mechanical buckling analysis of functionally graded graphene reinforcement composite laminated (FG‐GRCL) cylindrical panels stiffened by FG‐GRCL stiffeners is presented using Reddy's higher‐order shear deformation theory. The improved smeared stiffener technique is developed by applying the anisotropic higher‐order shear deformation beam theories for curved and straight stiffeners.